KAJIAN MATEMATIKA ISLAM - Evan Farhan Wahyu Puadi (Program Studi Pendidikan Matematika STKIP Muhammadiyah Kuningan, 2017)
Mathematics is a branch of philosophy. Its development is influenced by the results of human thought, so that the progress of a civilization becomes an implication of the results of these thoughts. The coming of Islamic teachings through the Messenger of Allah as a messenger of Allah SWT had a huge impact on the Arabian people at that time. Even the development is expanding to Europe and Asia. The spread of Islamic teachings throughout the world, giving birth to reliable thinkers, became the forerunner of the development of science, including mathematics. This research, provides an overview of how mathematics developed, and applied to the progress of civilization at that time. In addition, the literature study of the concepts of chemistry has been compiled by Muslim mathematicians at that time. In this case, it focuses on how arithmetic is discussed by Muslim mathematicians al-Uqlidisi about the concept of arithmetic.